Using the Brink Depth in Discharge Measurement for Inverted Semicircular Open Channels - Reham Zeidan; Mohamed Elshemy; Ibrahim Rashwan (Journal of Engineering Research - Egypt)
A free overfall at the end of an open channel provides a simple means for measuring flow discharge. The semicircular open channel plays a significant role in various applications, and it is of interest to calculate its discharge. This paper presents the application of the momentum equation to evaluate the use of a smooth inverted semicircular channel end as devised to calculate the discharge if the end depth is known. The experiments were performed in three separate semicircular inverted channels, with diameters of 15.0 cm, 18.4 cm, and 24.2 cm. The experimental data used to develop equations for calculating the discharge from known end depth. Where the end depth is related to the critical depth, and the end depth ratio value was found to be 0.8102 for a critical depth-diameter ratio of up to 0.40. On the other hand, the relationships for end depth ratio and non-dimensional discharge are defined. Two empirical equations are generated for the direct and indirect prediction of discharges from known end depth values.